2021
DOI: 10.3390/tropicalmed6040182
|View full text |Cite
|
Sign up to set email alerts
|

Association between Obesity and COVID-19 Mortality in Peru: An Ecological Study

Abstract: There is a gap in the epidemiological data on obesity and COVID-19 mortality in low and middle-income countries worst affected by the COVID-19 pandemic, including Peru. In this ecological study, we explored the association between body mass index (BMI), the prevalence of overweight and obesity, and the COVID-19 mortality rates in 25 Peruvian regions, adjusted for confounding factors (mean age in the region, mean income, gender balance and number of Intensive Care Unit (ICU) beds) using multiple linear regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
2
7
0
1
Order By: Relevance
“…In our study, the ORs for excess mortality occurred in a wider range of age groups for men (40–79 years old); this may be related to the high prevalence of chronic diseases in adult men, which increases the likelihood of death due to COVID-19 32 33. Thus, a recent study showed that as obesity prevalence increases, the COVID-19 MR increases in the Peruvian population ≥15 years 34. These factors may have contributed to a higher estimated excess all-cause death rate in men than women in the ≥60 years age group in Peru.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In our study, the ORs for excess mortality occurred in a wider range of age groups for men (40–79 years old); this may be related to the high prevalence of chronic diseases in adult men, which increases the likelihood of death due to COVID-19 32 33. Thus, a recent study showed that as obesity prevalence increases, the COVID-19 MR increases in the Peruvian population ≥15 years 34. These factors may have contributed to a higher estimated excess all-cause death rate in men than women in the ≥60 years age group in Peru.…”
Section: Discussionmentioning
confidence: 48%
“…32 33 Thus, a recent study showed that as obesity prevalence increases, the COVID-19 MR increases in the Peruvian population ≥15 years. 34 These factors may have contributed to a higher estimated excess all-cause death rate in men than women in the ≥60 years age group in Peru.…”
Section: Main Findingsmentioning
confidence: 99%
“…The factors that may have contributed to the causal relationship between all-cause excess mortality and COVID-19 mortality in Peru and the large differences in excess mortality from one region of Peru to another could have several explanations. First, mortality rates depend on social factors such as demographic and socio-economic characteristics, including age, population structure, population size, lifestyles, obesity prevalence, ethnicity, and the mobility of populations across between regions, as was observed in several countries, including Peru [ 2 , 12 , 22 , 23 ]. Second, mortality rates also depend on the probability of being infected, prevalence and incidence rates, and mortality among the infected population, since worldwide, Peru was the country with the highest number of COVID-19 deaths per 100,000 population [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Confounding factors included the mean age in the region (cases or deaths), mean income and gender balance (cases or deaths), and the number of intensive care unit (ICU) beds. These confounding factors were used in a previous observational study [ 12 ]. We also used COVID-19 vaccination coverage rates in individuals ≥ 18 years in 2021 as a confounding factor.…”
Section: Methodsmentioning
confidence: 99%
“…This excess mortality can be explained by social factors, individual factors, the health care system, and other direct and indirect factors related to COVID-19 infection. Several Peruvian studies have shown an association between obesity and COVID-19 mortality, both in the overall population and in patients infected with SARS-CoV-2 [ 12 , 13 ]. To control the COVID-19 pandemic and mitigate mortality associated with its complications, Peru launched the COVID-19 vaccination on 9 February 2021, which initially included immunization of health workers and subsequently encompassed the overall population [ 14 ].…”
Section: Introductionmentioning
confidence: 99%